Correction to: Effects of multi-component mixtures from sewage treatment plant effluent on common carp (Cyprinus carpio) under fully realistic condition - Giang, Pham Thai; Burkina, Viktoriia; Sakalli, Sidika; Schmidt-Posthaus, Heike; Rasmussen, Martin Krøyer; Randak, Tomas; Grabic, Roman; Grabicova, Katerina; Fedorova, Ganna; Koba, Olga; Golovko, Oksana; Turek, Jan; et al. (Environmental management, 2019)
The original version of this Article unfortunately contained an error. The authors' given and family names were transposed erroneously. It has been corrected now in this Erratum.